2011
DOI: 10.1371/journal.ppat.1002444
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Human Cytomegalovirus Locus Modulates Cell Type-Specific Outcomes of Infection

Abstract: Clinical strains of HCMV encode 20 putative ORFs within a region of the genome termed ULb′ that are postulated to encode functions related to persistence or immune evasion. We have previously identified ULb′-encoded pUL138 as necessary, but not sufficient, for HCMV latency in CD34+ hematopoietic progenitor cells (HPCs) infected in vitro. pUL138 is encoded on polycistronic transcripts that also encode 3 additional proteins, pUL133, pUL135, and pUL136, collectively comprising the UL133-UL138 locus. This work rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
292
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(304 citation statements)
references
References 44 publications
10
292
2
Order By: Relevance
“…During extensive passage in vitro, a 15 kb sequence in the UL/b' region (UL133-UL151) was deleted from the widely used HCMV laboratory strain AD169 compared with the low passage Toledo strain (8). In recent studies, the UL/b' region has been demonstrated to be important for the dissemination, latency and virulence of HCMV in human hosts (9)(10)(11)(12). The UL142 ORF, located within the UL/b' region, is 921 bp in length and is predicted to encode a protein, presumably an important component in the inhibition of natural killer (NK) cell killing and the innate defense against HCMV (13).…”
Section: Introductionmentioning
confidence: 99%
“…During extensive passage in vitro, a 15 kb sequence in the UL/b' region (UL133-UL151) was deleted from the widely used HCMV laboratory strain AD169 compared with the low passage Toledo strain (8). In recent studies, the UL/b' region has been demonstrated to be important for the dissemination, latency and virulence of HCMV in human hosts (9)(10)(11)(12). The UL142 ORF, located within the UL/b' region, is 921 bp in length and is predicted to encode a protein, presumably an important component in the inhibition of natural killer (NK) cell killing and the innate defense against HCMV (13).…”
Section: Introductionmentioning
confidence: 99%
“…This locus encodes four proteins, pUL133, pUL135, pUL136, and pUL138, from polycistronic transcripts (59,60). Like the entire ULb= region, the UL133-UL138 locus is dispensable for viral replication in fibroblasts (60).…”
mentioning
confidence: 99%
“…In HCMV, clinical strains contain a UL/b¢ region (UL128-UL150) that encodes multiple ORFs involved in cell-type dependent replication, intra-host dissemination, latency and immune evasion (Bradley et al, 2009;Cheung et al, 2005;Goodrum et al, 2007;Hahn et al, 2004;Penfold et al, 1999;Prod'homme et al, 2010;Ryckman et al, 2006Ryckman et al, , 2008Sinzger et al, 2008;Stanton et al, 2010;Tomasec et al, 2005;Umashankar et al, 2011). As viral determinants for HCMV entry of EP, UL128L-encoded proteins, form a pentamer with gH and gL mediating HCMV entry into EP via an endocytotic pathway (Bodaghi et al, 1999;Ryckman et al, 2008;Wang & Shenk, 2005;Wang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%